1984
DOI: 10.1016/0014-4886(84)90036-0
|View full text |Cite
|
Sign up to set email alerts
|

Relation between location of a motor unit in the human biceps brachii and its critical firing levels for different tasks

Abstract: Critical firing levels (CFLs) of single motor units (MU?.) in the long head of the human biceps brachii muscle were determined in combinations of two isometric tasks flexion of the elbow, supination of the lower arm, and exorotation of the humerus, as well as the corresponding antagonistic tasks. The MU activity was recorded by 25-pm bipolar wire electrodes. Four main patterns of MU recruitment, related to the recording location in the muscle, were found: (i) MUs active only when flexing the elbow were locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(107 citation statements)
references
References 24 publications
14
91
2
Order By: Relevance
“…1) did not show more similar values than the coefficients to the more distant electrodes. When regarding the activity of the four sites within the BB no significant difference between these four sites in the association to elbow flexion or forearm supination was apparent (see , although previous studies using intramuscular or multichannel EMG recordings indicated an inhomogeneous activity during the same type of contraction as in the current study (Perot et al, 1996;Staudenmann et al, 2013;ter Haar Romeny et al, 1984;van Zuylen et al, 1988). This discrepancy may be related to the limitation of conventional bipolar EMG which cannot extract muscular activity with the same precision as multichannel EMG (Staudenmann et al, 2010(Staudenmann et al, , 2013.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…1) did not show more similar values than the coefficients to the more distant electrodes. When regarding the activity of the four sites within the BB no significant difference between these four sites in the association to elbow flexion or forearm supination was apparent (see , although previous studies using intramuscular or multichannel EMG recordings indicated an inhomogeneous activity during the same type of contraction as in the current study (Perot et al, 1996;Staudenmann et al, 2013;ter Haar Romeny et al, 1984;van Zuylen et al, 1988). This discrepancy may be related to the limitation of conventional bipolar EMG which cannot extract muscular activity with the same precision as multichannel EMG (Staudenmann et al, 2010(Staudenmann et al, , 2013.…”
Section: Discussioncontrasting
confidence: 48%
“…Recordings of the BB were obtained from the proximal and distal portion of the two muscle heads, as distinct EMG activities of the two muscle parts were observed for specific contractions (Perot et al, 1996;Staudenmann et al, 2013;ter Haar Romeny et al, 1984;van Zuylen et al, 1988). Furthermore, the activity of the BR was recorded over the medial and lateral sides of the distal upper arm where the muscle becomes superficial, and the electrodes over the BRR were attached as displayed in Fig.…”
Section: Mechanical and Electrophysiological Recordingsmentioning
confidence: 99%
“…Assuming that the force twitch of a MU can be de scribed by a second-order linear low-pass system, former studies (ter Haar Romeny et al 1984) have obtained val ues for the time constant of the force twitch of MUs in the biceps brachii near 50 ms. However, a MU contributes to sinusoidal contractions with a sequence of APs, not with a single AP.…”
Section: Isometric Phase Relationmentioning
confidence: 99%
“…Measuring propagating waves on both the proximal and the distal side of the innervation zone would in such ideal cases be redundant and would not add information on muscle activity and muscle force. However, heterogeneity in muscle activity in the medio-lateral, but also some in longitudinal direction within BB has been reported during voluntary contractions (ter Haar Romeny et al, 1984;van Zuylen et al, 1988).…”
Section: Introductionmentioning
confidence: 99%